2002
DOI: 10.1093/jn/132.6.1720s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Antioxidants to Protect against DNA Damage in Adult Dogs

Abstract: We studied the effects of feeding an antioxidant blend of vitamins, minerals and carotenoids to a mixed adult dog population (n = 40, mean 4.4 +/- 1.85 y) for a 16-wk period. Compared to the control group of dogs (n = 20), the antioxidant (AOX)-supplemented group of dogs (n = 20) demonstrated significant increases in plasma levels of vitamin E and taurine by 4 wk of supplementation (P < 0.01) and total antioxidant activity (as measured by ferric-reducing antioxidant power assay) by 8 wk of supplementation (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
4
19
0
3
Order By: Relevance
“…In an effort to mitigate this possibility, dietary mitochondrial metabolites, antioxidants and a mixture of fruits and vegetables were fed to beagle dogs and it was demonstrated that this regime can reduce oxidative protein and DNA damage (Heaton et al, 2002) and prevent cognitive dysfunction (Conte et al, 2004;Cotman et al, 2002;Farr et al, 2003;Milgram et al, 2002) in aged dogs. We, therefore, hypothesized that this combination of dietary antioxidants and mitochondrial metabolites may reduce the magnitude of cellular losses seen in aged cochleae that result in age-related hearing loss and presbycusis.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to mitigate this possibility, dietary mitochondrial metabolites, antioxidants and a mixture of fruits and vegetables were fed to beagle dogs and it was demonstrated that this regime can reduce oxidative protein and DNA damage (Heaton et al, 2002) and prevent cognitive dysfunction (Conte et al, 2004;Cotman et al, 2002;Farr et al, 2003;Milgram et al, 2002) in aged dogs. We, therefore, hypothesized that this combination of dietary antioxidants and mitochondrial metabolites may reduce the magnitude of cellular losses seen in aged cochleae that result in age-related hearing loss and presbycusis.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that mineral supplementation in the animal being vaccinated may be an important additive especially in post bite cases of rabies wherein an early antibody response is of utmost importance for the preventing the mortalities. Similarly, significantly greater (P<0.05) production of rabies specific antibodies at 2, 4 and 6 weeks post vaccination in group of dogs supplemented with antioxidant nutrients as compared to the control group was recorded (Heaton et al 2002). Proper functioning of immune system requires appropriate levels of macro as well as micro minerals to be included in the diet of animals.…”
Section: Resultsmentioning
confidence: 88%
“…U kotretmanu, uzorci su istovremeno tretirani vodonik-peroksidom u koncentraciji od 100 μM i Sal B u tri različite koncentracije (12,5 može sprovoditi na gotovo svakom tipu ćelija kao i na leukocitima periferne krvi koji su predmet tretmana u ovom radu. Komet testom se mogu uspešno proceniti interakcije antioksidanasa i genotoksičnih agenasa (23), a pouzdano se koristi i za ispitivanje efekta određenih supstanci na očuvanje integriteta genetičkog materijala (24,25,26). Komet test su prvobitno razvili Ostling i Johanson (27) …”
Section: Materijal I Metodeunclassified